DARWIN, ECOLOGICAL PSYCHOLOGY, AND THE PRINCIPLE OF ANIMAL-ENVIRONMENT MUTUALITY - Costall, Alan (Psyke & Logos, 2001)
... traditional theories have separated life from nature, mind from organic life, and thereby created mysteries. ... Those who talk most of the organism, physiologists and psychologists, are often just those who display least sense of the intimate, delicate and subtle interdependence of all organic structures and processes with one another. The world seems mad in pre-occupation with what is specific, particular, disconnected in medicine, politics, science, industry, education. ... To see the organism in nature, the nervous system in the organism, the brain in the nervous system, the cortex in the brain is the answer to the problems which haunt philosophy. And when thus seen they will be seen to be in, not as marbles are in a box but as events are in history, in a moving, growing never finished process (John Dewey, 1958, pp. 278 & 295).